War Stories: Narrative Sense-Making in German Eastern Front Soldier Memoirs - Hope Sneddon; Jesper Gulddal ([sic])
While historians have long acknowledged the textual and rhetorical aspects of their sources, the genre of the soldier memoir is still discussed mainly in terms of its psychological or factual veracity, and there is lack of understanding of how memories are reconfigured when passed through the interpretive medium of narrative. In this paper we present a discussion of the structure and functions of narrative in three German World War II soldier memoirs: Willy Peter Reese´s Mir selber seltsam fremd (1944/2004), Gottlob Herbert Biedermann´s Krim-Kurland mit der 132. Infanterie-Division 1941-45 (1964), and Edgar Klaus´s Durch die Hölle des Krieges (1991). Written at various distances from the war, these memoirs represent successive stages of coming to terms with the horrors and crimes of the Eastern Front. However, as we argue, this work of memory is mediated by narrative, and the plotting and narrative sequencing of the soldier memoir often tell a story that runs counter to the author´s stated views. A narrative approach is therefore indispensable for understanding the specific way in which soldier memoirs capture and communicate the experience of war.